Dysregulation of iron metabolism modulators in virologically suppressed HIV-infected patients - Garrido-Rodríguez, Vanesa; Álvarez-Ríos, Ana Isabel; Olivas-Martínez, Israel; Pozo-Balado, María del Mar; Bulnes-Ramos, Ángel; Leal, Manuel; Pacheco, Yolanda María (Frontiers in Immunology, 2022)
Background Iron metabolism plays an essential role in cellular functions. Since virologically suppressed chronic HIV-infected subjects under effective antiretroviral treatment (ART) exhibit a persistent immune dysfunction that leads to comorbidities, iron homeostasis may be relevant in this context. We aimed to explore iron metabolism in virologically suppressed chronic HIV infected subjects under a successful ART. Methods In this retrospective study, traditional iron metabolism biomarkers (total iron, ferritin, transferrin, and transferrin saturation index), as well as soluble transferrin receptor (sTfR), hepcidin, and inflammatory markers were determined in virologically suppressed chronic HIV-infected subjects under at least 2 years of ART (HIV) who also had >350 CD4-T-cells/mm3 (N=92) from Spain. As controls, we collected non-HIV age-matched healthy donors (Young, N=25) and elderly subjects (>65 years old; Elderly; N=25). Additionally, an external group of non-HIV patients with ferritin<50 ng/mL diagnosed with absolute iron deficiency (Ferropenic group; N=84) was included. Comparisons between groups were performed using Kruskal-Wallis or Mann-Whitney U-tests, while associations between variables were explored by Spearman’s rho correlation coefficient. Results We selected samples from HIV-infected subjects (aged 42[34-47], 95% males), young age-matched (aged 40[30-58], 60% males), and elderly controls (aged 82[78-88], 100% males). Compared to both healthy (Young and Elderly) groups, HIV exhibited decreased iron, transferrin saturation, and sTfR, and increased ferritin, but similar hepcidin levels. Notably, associations between sTfR and iron (Young, r=-0.587, p=0.002; Elderly, r=-0.496, p=0.012) or transferrin saturation index (Young, r=-0.581, p=0.002; Elderly, r=-0.489, p=0.013) were negative in both controls while positive in HIV (r=0.464, p<0.0001 and r=0.421, p<0.0001, respectively). Moreover, the expected negative correlation between hepcidin and sTfR, observed in controls (Young, r=-0.533, p=0.006; Elderly, r=-0.473, p=0.017), was absent in HIV (r=0.082; p=0.438). Interestingly, the HIV inflammatory profile differed from the Elderly one, who despite their inflammaging-related profile, succeed in maintaining these associations. Furthermore, subjects from the ferropenic group (aged 42[32-51], 5% males), showing significantly lower levels of hepcidin and higher sTfR, as expected, reflected similar correlations as those Young and Elderly, in contrast to HIV. Conclusions Virologically suppressed chronic HIV-infected patients under successful ART exhibit altered levels of iron metabolism modulators suggesting a complex functional iron deficiency.